Additive based on synthetic aluminosilicate for cement systems - Логанина, Валентина Ивановна; Жерновский, Игорь Владимирович; Садовникова, Мария Анатольевна; Жегера, Кристина Владимировна (Eastern-European Journal of Enterprise Technologies, 2013)
For regulating the structure and properties of lime-based and cement-based composites it was proposed to add synthetic aluminosilicates to the composition. Aluminosilicates were synthesized in acidic medium by means of their precipitation from the aluminum sulfate Al2 (SO4)3 solution and adding sodium silicate followed by washing the precipitate. It is shown that synthesized aluminosilicates are characterized by a high activity, being more than 350 mg/g. The specific surface area of powder, determined by the BET method, constitutes Ssp = 86.5 ± 3.5 m2/g. During the X-ray diffraction analysis of the composition it was determined that there is a crystalline phase (22%), represented by thenardite and gibbsite, as well as an amorphous component, represented by nanoscale cristobalite-like crystallites (78%). During the introduction of synthetic aluminosilicates into the lime composites, increased amount of chemically-bound lime and higher compressive strength can be observed. It is shown that the composite cement binder, containing synthetic aluminosilicates, is characterized by less setting time.